1939
DOI: 10.1021/ja01875a519
|View full text |Cite
|
Sign up to set email alerts
|

On the Color Reaction for Vitamin K

Abstract: Communications to the Editor 1613 In our previous communication (¡oc. cit.) we gave an extinction coefficient of = 385 at 248 niju for vitamin Ki but since that time a value of 540 has been obtained. The analyses of both preparations indicated that each was analytically pure. Our first value was probably due to instability of the vitamin on storage and toward light. For this reason we are not at present certain that 540 is the maximum value attainable. In this same communication line 38 column 1 should read "a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1940
1940
1982
1982

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…With the exception of 2,3dimethyl-1 ,4-naphthoquinone, activity began to appear as the alkyl groups were increased in size beyond six to eight carbon atoms, became appreciable in the 2-methyl-3-cinnamyl (ten carbons) and 2-methyl-3geranyl (eleven carbons) compounds, and reached a peak in vitamin K1 (twenty-one carbons) and vitamin K2 (thirty-one carbons), Fernholz et al (73) pointed out that the inactivity of 2-n-octadecyl, 2-methyl-3-noctadecyl, and similar long-chain substituted 1 4-naphthoquinones does not fit into this picture. From his study of a series of 2 3-dialkyl-1 ) 4-naphthoquinones, Fieser (78) reported a certain specificity in structure associated with antihemorrhagic activity.…”
Section: -Methyl-3-benzyl-l 4-naphthoquinone (78 87) 2-methyl-3-tmentioning
confidence: 97%
See 2 more Smart Citations
“…With the exception of 2,3dimethyl-1 ,4-naphthoquinone, activity began to appear as the alkyl groups were increased in size beyond six to eight carbon atoms, became appreciable in the 2-methyl-3-cinnamyl (ten carbons) and 2-methyl-3geranyl (eleven carbons) compounds, and reached a peak in vitamin K1 (twenty-one carbons) and vitamin K2 (thirty-one carbons), Fernholz et al (73) pointed out that the inactivity of 2-n-octadecyl, 2-methyl-3-noctadecyl, and similar long-chain substituted 1 4-naphthoquinones does not fit into this picture. From his study of a series of 2 3-dialkyl-1 ) 4-naphthoquinones, Fieser (78) reported a certain specificity in structure associated with antihemorrhagic activity.…”
Section: -Methyl-3-benzyl-l 4-naphthoquinone (78 87) 2-methyl-3-tmentioning
confidence: 97%
“…On a molecular basis, sodium 1 ,4-naphthohydroquinone disulfuric acid ester is one-third as active as the quinone itself. The method of Barbot (34) has been used by Fernholz et al (73) and by Karrer et al (118) for the production of p-substituted tetralins. On the other hand, Ansbacher (32) reports that it is less active than the parent quinone or hydroquinone.…”
Section: Potent Water-soluble Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1935 Hermann (5) and Hermann and Kassowitz (6) reported a marked fall of blood sugar in animals and patients following the application of an insulin salve to the skin. Major (7) in 1935 and 1936 (8, 9) concluded that under proper conditions insulin could be…”
Section: Studies On the Cutaneous Absorption Of Insulin*mentioning
confidence: 99%
“…Of the several procedures (6)(7)(8)(9)(10)(11)(12)(13)(14) for the estimation of menadione the method of Menotti (10) seems to be the most promising one. The determination is based on the sensitive color test for 2-methyl-l,4-naphthaquinone and related substances as reported by Novelli (9).…”
mentioning
confidence: 99%